2018
DOI: 10.3390/ijms19061725
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Plant-Mediated Synthesis of Metallic Nanoparticles: A Systematic Review

Abstract: In the field of medicine, nanomaterials, especially those derived using the green method, offer promise as anti-cancer agents and drug carriers. However, the biosafety of metallic nanoparticles used as anti-cancer agents remains a concern. The goal of this systematic review was to compare the cytotoxicity of different plant-mediated syntheses of metallic nanoparticles based on their potency, therapeutic index, and cancer cell type susceptibility in the hopes of identifying the most promising anti-cancer agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 79 publications
1
48
0
Order By: Relevance
“…L929 cells were seeded at 3 × 10 3 cells/mL into 96-well plates containing 100 µL of medium (Hanan et al, 2018;Poobalan et al, 2018). Next, 50 µL of diluted NT and DEET at different concentrations were added to the cells.…”
Section: Sample Dilutionmentioning
confidence: 99%
“…L929 cells were seeded at 3 × 10 3 cells/mL into 96-well plates containing 100 µL of medium (Hanan et al, 2018;Poobalan et al, 2018). Next, 50 µL of diluted NT and DEET at different concentrations were added to the cells.…”
Section: Sample Dilutionmentioning
confidence: 99%
“…Currently, nanomedicine is a field that has great interest in the scientific community [1], since it has found application in many areas of science such as medical imaging [2], tumor targeting [3], drug delivery [4,5], and biosensors [6], among others. Particularly, nanoparticles have been widely studied for medical purposes; however, the main problem consists in finding the materials with optimal biocompatibility [7]. It has been found that gold nanoparticles (AuNPs) are one of the most innocuous nanoparticles for living organisms [8], and it is suspected that most of the nanoparticles enter into the cells by endocytosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…The DMP samples were analysed by DLS using a zetasizer (Nano ZS, Malvern Instruments, Worcestershire, UK) to evaluate the mean diameter and zeta potential of the nanoparticles. SEM and TEM were used to analyse the morphology of the nanoparticles [42,43]. DMP2 was chosen for the drug release study based on the results of a loading efficiency analysis.…”
Section: Preparation Characterisation and In Vitro Drug Release Studmentioning
confidence: 99%